Сравнение процессов суверенизации Крыма и Каталонии - Ksenzova V. S. (Education and science in the modern context, 2018)
Two very similar in essence people's referendum on their future fate - in the Crimea and in Catalonia - dispersed in the main: how the outcome of the people's will was reacted by those who were trusted by their future
Keywords: референдум; Крым; демократизация; суверенитет; government; Правительство; crimea; sovereignty; декларация; referendum; Каталония; провозглашение; Catalonia; proclamation; democratization; declaration